The effects of firm efficiency and production decisions on inventory write-down: Evidence from taiwanese manufacturing companies - Chan Y.C.; Kweh Q.L.; Wang W.-K. (2023)
This purpose of this study is to examine the determinants of inventory write-down decisions including firm efficiency and production decisions. Data envelopment analysis (DEA) is used to proxy for firm efficiency while change in percent added to inventory (CPAI) is used to proxy for overproduction. We utilize Taiwanese manufacturing companies listed on Taiwan Stock Exchange (TWSE) and with data available in Taiwan Economic Journal (TEJ) database as the sample in this study. Results show that firm efficiency has significant positive relationship with inventory write-down indicating managers exercise reporting flexibility to engage in accrual manipulation. However, we do not find significant association between overproduction and inventory write-down to support the real earnings management hypothesis. IDOSI Publications, 2013.